Transformative Justice for Elimination of Barriers to Access to Justice for Persons with Psychosocial or Intellectual Disabilities - Jonas Ruškus (Laws, 2023)
By adopting the Convention on the Rights of Persons with Disabilities (the CRPD) in New York, the United Nations heralded a new epoch on how disability-related matters ought to be comprehended and addressed across the globe. The aim of this article is to argue the role and substance of the CRPD, under which each State Party has a responsibility and duty to protect, promote and implement access to justice for all persons with disabilities on equal bases with others. Systemic and structural barriers to access to justice that are faced by persons with psychosocial or intellectual disabilities are highlighted, and the determinants of them are identified including boundaries of the principle of formal equality. The human-rights-based response within the framework of obligations of the States Parties of the CRPD to ensure access to justice for persons with psychosocial or intellectual disabilities is argued, with specific consideration of the principle of transformative equality. The analysis is based on the CRPD Committee’s jurisprudence, including Concluding observations for the States Parties, General Comments, statements and guidelines.